HUBUNGAN KADAR HbA1c DENGAN TEKANAN DARAH TINGGI PADA PASIEN DIABETES MELITUS TIPE- 2 DI RUMAH SAKIT SANTA ELISABETH LUBUK BAJA KOTA BATAM PERIODE JANUARI – OKTOBER 2023 - Edward, Zulkarnain; Bratasena, Bratasena; Parmaditta, Ochavia (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2024)
Background: Glycated hemoglobin or HbA1c has become the gold standard for long-term glycemic measures. People with diabetes mellitus must keep blood glucose levels under control to prevent various complications that can occur. High blood pressure is a high risk factor for diabetic complications. Methods: This study is a type of quantitative research with analytic observation method and cross sectional approach. Data were taken from medical records for the period January - October 2023 at Santa Elisabeth Hospital Lubuk Baja Batam City. The sampling technique was total sampling with a total sample size of 77 patients. The results of the study were analyzed by frequency distribution and then tested with the spearman rank correlation test. Results: Based on the Spearman rank correlation test, the probability value (p-value) is <0.001, because the p-value is smaller than 0.05, it is concluded that there is a relationship between HbA1c levels and high blood pressure, where the correlation value (r) is 0.719 which means it has a strong relationship with a positive direction. Conclusion: There is a significant relationship between HbA1c levels and high blood pressure in patients with type 2 diabetes mellitus at Santa Elisabeth Lubuk Baja Hospital, Batam City.